Tadpoles Inhabiting Natural and Anthropogenic Temporary Water Bodies: Which Are the Environmental Factors that Affect the Diversity of the Assemblages? - Camacho-Rozo, Claudia Patricia; Urbina-Cardona, Nicolás (Frontiers in Environmental Science, 2021)
The study of tadpole assemblages allows inferring habitat availability and using their occupation as a means of proxy for the effective reproduction of the species, contributing to complementary information for the study of their adult forms. Environmental variables, represented by abiotic variables, vegetation structure, matrix management, and landscape elements, affect species having reproductive modes associated with oviposition and development in bodies of water. In the Orinoco region, most amphibians have complex life cycles and deposit their eggs in highly dynamic lentic bodies of water. Therefore, it is important to know how larval assemblages change over short periods of water accumulation and their relationship with environmental variables. Fieldwork was conducted during 9 weeks of larval sampling, from the beginning of the rainy season. We evaluate changes in anuran assemblages associated with water accumulation in five temporary water bodies of anthropogenic (road or pasture) and natural (savanna or gallery forest) origin. Twenty environmental variables were evaluated and measured in the center of each water body. Of these, nine landscape variables were measured only once during the study. The other eleven variables, representing management practices, physicochemical and structural characteristics of the water bodies, were measured weekly during the 3 months of sampling. We explored differences in the structure and diversity of larval-stage anuran assemblages using statistical tests suitable for small sample sizes (i.e., permutational multivariate analysis of variance PERMANOVA and the distance-based linear modeling DistLM). Of the 14 species found, two species had remarkedly high abundances from which Rhinella humboldti (19% of the total tadpole abundance) was a generalist inhabiting the natural and anthropogenic water bodies, while Leptodactylus insularum (18% of the total tadpole abundance) was a specialist at a natural pond in the savanna. The natural water bodies contained the highest number of species (between 10 and 12) and a total abundance of larvae (between 847 and 485 individuals). In contrast, the anthropogenic water body tracks generated by tractors were only occupied by two species with 50 individuals in total, while the water body generated by the trampling of cattle in pastures had three species with 474 individuals. These three species that inhabited the anthropogenic puddles were also found in the natural ponds and none of the eight species of hylids inhabited the puddles. In each field trip, all the tadpoles were collected from the sampled bodies of water. However, a week later, we found that each of the water bodies had been recolonized by four species (Leptodactylus fuscus, Leptodactylus fragilis, Elachistocleis ovalis, and R. humbolti). The variables with the highest explanatory power on the variation of anuran assemblage structure throughout all the water bodies were height of plants, number of cattle, distance to the nearest native forest edge, distance to an anthropic lentic body of water, distance to a natural lentic body of water, and pH. The bodies of water immersed in the natural cover were more diverse and had a greater degree of spatial and temporal species turnover. Our study calls for the importance of understanding the turnover of larval stage anurans over short periods, associated with water accumulation, in highly dynamic systems such as natural ponds and anthropogenic puddles. The importance of species traits and local processes is also highlighted, from environmental variables to human management activities, in the conservation of amphibian assemblages.